2022
DOI: 10.1002/jsf2.50
|View full text |Cite
|
Sign up to set email alerts
|

A chromatographic method to monitor fructan catabolism in two cool‐season grasses fermented by mixed bovine ruminal microbiota

Abstract: BACKGROUND: Cool-season grasses contain fructans (fructose-based polymers), whose monomers are linked by β-2,6 or β-1,2 bonds. Fructans in the rumen are hydrolysed to fructose by bacterial enzymes, but little is known about the kinetics of fructan catabolism in the rumen. A chromatographic method, using high-performance anion-exchange chromatography (HPAEC) with pulsed amperometric detection, was developed to monitor changes in fructan profiles during the in vitro fermentation of timothy (Phleum pratense L.) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 26 publications
3
8
0
Order By: Relevance
“…These extracts were put through end‐capped C 18 solid‐phase extraction columns (Clean‐Up, United Chemical Technologies, Bristol, PA, USA) containing 100 mg sorbent. Columns were conditioned with methanol and water as described by Kagan et al (2022), after which 0.9 mL of sample was vacuum‐filtered through the column and collected. SPE‐cleaned filtrates were stored at −20°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…These extracts were put through end‐capped C 18 solid‐phase extraction columns (Clean‐Up, United Chemical Technologies, Bristol, PA, USA) containing 100 mg sorbent. Columns were conditioned with methanol and water as described by Kagan et al (2022), after which 0.9 mL of sample was vacuum‐filtered through the column and collected. SPE‐cleaned filtrates were stored at −20°C until analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Columns were conditioned with methanol and water as described by Kagan et al (2022), after which 0.9 mL of sample was vacuum-filtered through the column and collected. SPE-cleaned filtrates were stored at À20 C until analysis.…”
Section: Wsc Extraction and Preparation For Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the relevance of fructans in ruminant nutrition, research evaluating ruminal degradation of fructans is relatively limited. Overall, there are indications that DP may influence fermentation [19][20][21][22]. While specific bacteria may have differential capacities for degrading higher-DP long-chain fructans or lower-DP short-chain fructans [19,21], mixed bacteria harvested from equine digesta have been shown to degrade long-chain fructans prior to short-chain fructans [20].…”
Section: Introductionmentioning
confidence: 99%
“…While specific bacteria may have differential capacities for degrading higher-DP long-chain fructans or lower-DP short-chain fructans [19,21], mixed bacteria harvested from equine digesta have been shown to degrade long-chain fructans prior to short-chain fructans [20]. More recently, Kagan et al [22] found bovine rumen bacteria degraded long-chain fructan within the first two hours of fermentation, which was coupled with an increase in short-chain fructans, suggesting hydrolysis of long-chain fructans to short-chain fructans prior to subsequent degradation.…”
Section: Introductionmentioning
confidence: 99%